Parallel algorithms for LU decomposition on a shared memory multiprocessor - Kaya, D; Wright, K (Elsevier Science Inc, 2005)
In this work, we present the numerical results (using C++) obtained from seven different versions of the LU decomposition algorithms. Four of the algorithms use Crout-like reduction and three of the algorithms use Doolittle-like reduction. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: the LU decomposition method; parallel algorithms; shared memory multiprocessor